Analysis of Student’s Interest Following Passing Material on Futsal Extracurricular at SMP Negeri 03 Muaradua Kisam - Rio, Muhammad Eka; Manullang, Jujur Gunawan; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
Futsal is a team sport where each team has 5 players. There are so many factors that affect students’ interest in futsal sports such as factors from within themselves and from outside themselves in the form of encouragement from the closest people, as well as the environment. This study aims to determine the extent of students’ interest in participating in extracurricular futsal at SMPN 03 Muaradua Kisam. This research is quantitative descriptive research with a questionnaire approach. The population in this study was all futsal extracurricular students, while sampling in this study was by using the Saturated sampling method, where all members of the population were used as samples, totaling 30 people. The analysis technique in this study is a descriptive analysis technique with a quantitative approach, then the research data is analyzed by statistical methods, while the calculation of questionnaire data uses percentages with tables and graphs. From the results of the research that has been done, it can be concluded that the interest of students in participating in extracurricular futsal at SMPN 03 Muaradua Kisam from a population of 30 students who got Very High scores amounted to 16 students with a percentage (53%), High scores amounted to 10 students with a percentage (33%), Medium grades amounted to 2 students with a percentage (7%), Low grades amounted to 1 student (3%), Very Low student grades amounted to 1 student with a percentage (3%).